Is Inclusion of informed consent associated with HIV seropositivity rate? findings from 2017 HIV sentinel surveillance among men having sex with men in select states of India - Partha Haldar; Shreya Jha; Ramashankar Rath; Kiran Goswami; Nishakar Thakur; Pradeep Kumar (Indian Journal of Public Health, 2020)
Background: During round 2017 of HIV Sentinel Surveillance (HSS) for men who have sex with men (MSM) in India, sampling strategy was changed from consecutive sampling to random sampling, and recruitment was conditioned on informed written consent. Objective: The study aimed to explore whether inclusion of informed consent is associated with HIV seropositivity rates among MSM population in select four states of Central India. Methods: The cross-sectional study was conducted in four states of Delhi, Jharkhand, Uttar Pradesh, and Uttarakhand that were supervised by All India Institute of Medical Sciences, New Delhi. We did analysis of data collected during 2017 HSS, supplemented with additional program data from targeted intervention (TI) sites. All nine MSM sites in four states were included. Participants were defined as all those MSM who participated in HSS 2017 irrespective of whether they were mentioned in the random list or were selected by the TI partner. The MSM in the random list who either refused to participate or could not be contacted even after three attempts were classified as “nonparticipants.” Seropositivity of both groups was compared. Descriptive statistics were derived. Results: Overall nonparticipation rate was 14.7%, the highest being in Jharkhand (26%) and lowest in Uttarakhand (6.8%). Overall HIV positivity rate was significantly higher (P < 0.001) in nonparticipants (4.2%) when compared to participants (1.42%). Conclusion: The change in sampling strategy and introduction of written informed consent for recruitment of high-risk groups in HSS 2017 round could have led to an underestimation of HIV seropositivity rate among MSM in the states in Central Zone.